Hubungan Anemia, Status Gizi, Dan Jarak Kehamilan Pada Ibu Hamil Terhadap Kejadian Berat Bayi Lahir Rendah (BBLR): Relationship of Anemia, Nutritional Status, and Interval of Pregnancy in Pregnant Women to the Incidence of Low Birth Weight (LBW) - Hasanah, Nurul; Tambunan, Novrida (Dohara POAJ, 2023)
Introduction: LBW is the highest predictor of infant mortality, especially in the first month of life. LBW babies have a 20 times greater risk of death compared to babies born with normal weight. The purpose of this study is to the relationship between anemia, nutritional status, and pregnancy intervals in pregnant women on the incidence of low-birth-weight babies (LBW) at Cimacan Hospital in 2022. Methods: Retrospective Descriptive research design. In this study, the population was mothers who gave birth at Cimacan Hospital in January-June 2022 as many as 341 people. The sample in this study was 77 respondents in this study using a purposive sampling technique. Researchers used the Chi-Square test. Results: Based on the results of research on the relationship between anemia in pregnant women and the incidence of low-birth-weight babies (LBW) the p-value = 0,000 was obtained. The relationship between nutritional status in pregnant women and the incidence of low-birth-weight babies (LBW) obtained a p-value = 0,000. The relationship between pregnancy spacing in pregnant women and the incidence of low-birth-weight babies (LBW) obtained a p-value = 0,000. Discussion: The conclusion is that there is a relationship between anemia, nutritional status, and pregnancy intervals in pregnant women to the incidence of low-birth-weight babies (LBW) at Cimacan Hospital in 2022. Suggestions for health workers to carry out health promotion through placing billboards, counseling both individually and in groups, and can conduct health education for pregnant women through classes on pregnant women especially the problem of balanced nutrition during pregnancy to avoid LBW.